1981
DOI: 10.1210/endo-108-4-1142
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Degradation by Hepatocytes in Primary Culture*

Abstract: The mechanism by which the liver degrades insulin has not yet been completely clarified. In intact, non-"leaky" cells the primary process seems to be mediated by initial receptor binding. We now demonstrate that isolated rat hepatocytes in primary culture are suitable for examining insulin degradation. Hepatocytes did not leak degrading activity into the medium, and thus, the degradation seen was essentially exclusively cell mediated. [125I]Iodoinsulin degradation by these cells was dependent on time and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 10 publications
3
26
0
Order By: Relevance
“…IDE is a 110-kDa zinc-and thiol-dependent peptidase present in the cytosol and peroxisomes and on the cell surface of a wide variety of cell types including neurons (25)(26)(27). Because of its K m for insulin in the nanomolar range, IDE is involved in the degradation of this hormone in vivo (28). Yet IDE is also capable of degrading many small peptides of unrelated sequence, several of which show amyloidogenic potential in vitro and in vivo such as glucagon, amylin, calcitonin, atrial natriuretic peptide, and A␤, including all the genetic variants of A␤ associated with dementia or stroke (for reviews, see Refs.…”
mentioning
confidence: 99%
“…IDE is a 110-kDa zinc-and thiol-dependent peptidase present in the cytosol and peroxisomes and on the cell surface of a wide variety of cell types including neurons (25)(26)(27). Because of its K m for insulin in the nanomolar range, IDE is involved in the degradation of this hormone in vivo (28). Yet IDE is also capable of degrading many small peptides of unrelated sequence, several of which show amyloidogenic potential in vitro and in vivo such as glucagon, amylin, calcitonin, atrial natriuretic peptide, and A␤, including all the genetic variants of A␤ associated with dementia or stroke (for reviews, see Refs.…”
mentioning
confidence: 99%
“…Finally, several agents (i.e., bacitracin and suifhydryl modifying reagents), which inhibit the activity of this enzyme, inhibit insulin degradation in the intact cell (24)(25)(26). However, these agents are not specific for the IDE.…”
mentioning
confidence: 99%
“…Lysosomes may be implicated in the intracellular degradation of insulin. However, current studies have demonstrated that chloroquine, a lysosomal inhibitor, has little effect on 125I-insulin degradation in various tissues [4,15,20,21], suggesting that lysosomes may have only a small role in the process of insulin degradation. On the contrary, IDE accounts for most of the insulin-degrading activity of various cell extracts [9,12,15].…”
Section: Discussionmentioning
confidence: 87%
“…This loss of cell surface receptors may be linked with hormone internalization, because after insulin binds to its receptors, insulin-receptor complexes are intemalized by absorptive endocytosis [2,3]. Following this, insulin seems to be degraded in the intracellular sites [4][5][6]. Although the degradation of insulin has been extensively studied, the sites and enzymes of intracellular degradation have still not been determined.…”
mentioning
confidence: 99%